Clouds - Bauer, Marion Dane.; Wallace, John, 1966- (New York : Aladdin, 2005)
Illustrations and simple text explain three types of clouds, stratus, cumulus, and cirrus.
G1
Keywords: Clouds -- Juvenile literature; Clouds